Effect of Doping and Temperature Operating on (NO2 ) Gas Sensing Properties for MgxZnO1-x /n-Si Heterojunction - O. Abdulazeez, Mousa; H. Trier, Saleem (Al-Qadisiyah Journal of Pure Science, 2018)
In this paper prepared ZnO/n-Si, and dopant Mg0.05ZnO0.95/n-Si films using a chemical spraying pyrolysis (CSP) technique. The grow doped solutions Mg0.05ZnO0.95 volumetric ratio (5)% from MgO and deposited on silicon substrates and at different temperatures (400,450,and 500)°C was installed thickness by installing a number of sprays. The thickness of all the films ranges between (80 ±5) nm, used as a gas holder nitrogen. The crystal structure was examined by using X-ray diffraction(XRD) technique. The results showed that all the prepared films polycrystalline, showing improvement in the crystal structure in terms of increasing the intensity of the peaks, by change of temperature. As studied the topography of the surface of the films prepared using field emission scanning electron microscopy (FESEM), and energy dispersive X-ray (EDX), and atomic force microscope (AFM), granular size for the ZnO depends on the ratio of Mg-content volumetric, where decreases grain size with adding Mg-content. As well as that add MgO in the films lead to a decrease in surface roughness. Also, (EDX) showed films contain elements (Si, N, O, Zn, and Mg) as expected. The sensitivity of the prepared films to (NO2) gas in air ambient has been measured in the gas sensing system. All samples were tested at a ratio (3% NO2:air) and bias voltage (6Volt). The best ratio dopant of the Mg-content is (5)% , best operating temperature is (200)oC, and best temperature of the silicon substrate is (400)°C. The maximum sensitivity is (90.80)% and fast response time is((6.3s) and recovery time is (44.1s).